Fenomena Hate Speech di Sosial Media dalam Perspektif Psikologi Islam - Isyatul Mardiyati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
Hate speech more improve along with internet technology advance development. Less of controlling and low of self controlling ability to deviant behaviour,potential turning somebody with good attitude into hater speech. Frequently, the impact of this behaviour making hater deals with criminal law. Even among of them crouch in prison. Then, hate speech phenomenon becomes one of crime cyber matter replied of human thoughts tendency using negative emotional to response a problem. In the other side hate speech also can disturbing positive soul of somebody and turning somebody filled with negative aura.